British political history 1867 - 2001 ; democracy and decline - Pearce, Malcolm; Stewart, Geoffrey 1945- (Routledge, 2002)
Tackling broad themes and offering a fresh view of British history, this book sets politics within the wider cultural, economic and social contexts. It is a thought-provoking text which bridges the gap between A-level and higher education.
Keywords: Geschichte 1900-2000; Geschichte 1867-1995; Politieke geschiedenis; Politieke situatie; Geschichte; Politik; Politische Situation; Grande-Bretagne - Histoire - 1837-1901 (Vic.); Grande-Bretagne - Histoire - 20e siècle; Grande-Bretagne - Politique et gouvernement - 1837-1901; Grande-Bretagne - Politique et gouvernement - 20e siècle; Großbritannien; Great Britain -- History -- 20th century; Great Britain -- History -- Victoria, 1837-1901; Great Britain -- Politics and government -- 1837-1901; Great Britain -- Politics and government -- 20th century